Islam and Modernisme di Indonesia: Kontribusi Pemikiran Mohammad Rasjidi (1915-2001) - Mohammad Zakki Azani; Khalif Muammar A. Harris (Universitas Darussalam Gontor, 2019)
AbstractSince Indonesia gained its independence in 1945, several Indonesian scholars have attempted to build and re-develop various aspects of developmental fields including education, economy, and society. In developing a country with the world's largest Muslim-majority population, one of their main concern is the revival of Islamic thought at Islamic higher institutions in Indonesia. This revival of thought involves re-interpreting important elements of Islamic thought based upon the secular, Western and modern way of thinking. This effort, known as the modernization of Islamic thought, has led to severe confusion and misunderstanding. Mohammad Rasjidi employed the framework of ahl al-sunnah wa al-jamā‘ah to criticize and subsequently reject secularisation as a philosophical program which was used as the foundation for the modernization of Islamic thought. This paper elaborates the significant roles of Mohammad Rasjidi’s thoughts and contributions in correcting and re-affirming the fundamental principles of Islam, specifically concerning the nature of man, the nature of human reason, the nature of morality and the understanding of the state, all of which conforms with the Worldview of Islam.Keywords: Mohammad Rasjidi, Islam and Modernism; the nature of nan; revelation, reason, morality, state.AbstrakSetelah Indonesia meraih kemerdekaan pada tahun 1945, beberapa cendekiawan di Indonesia mencoba untuk membina dan membangun kembali dalam perbagai bidang pembangunan termasuk pendidikan, ekonomi dan sosial. Dalam suasana negara yang sedang membangun dengan penduduk mayoritas Muslim terbesar di dunia, salah satu aspek yang menjadi tumpuan ialah pembaharuan pemikiran Islam di pendidikan tinggi Islam Indonesia. Pembaharuan pemikiran ini melibatkan penguraian kembali tentang unsur penting pemikiran Islam dengan cara berfikir modern Barat yang sekuler. Upaya ini dinamakan sebagai modernisasi pemikiran Islam yang mengakibatkan kekeliruan dan kesilapan pemahaman. Rasjidi menggunakan kerangka ahl al-sunnah wa al-jamā’ah dalam membahas sekularisasi sebagai program filsafat yang dijadikan sebagai asas modernisasi pemikiran Islam. Makalah ini menguraikan kontribusi penting pemikiran Mohammad Rasjidi dalam mengoreksi dan menegaskan kembali beberapa prinsip Islam berkenaan–hakikat insan, akal, akhlak dan paham negara—agar tidak bertentangan dengan Pandangan alam Islam (the Worldview of Islam).Kata Kunci: Mohammad Rasjidi; Islam dan modernisme; hakekat insan; wahyu; akal; akhlak; negara.